Risk-adjusted forecasts of oil prices - Patrizio Pagano; Massimiliano Pisani (European Central Bank (ECB), 2009)
This paper documents the existence of a significant forecast error on crude oil futures. We interpret it as a risk premium, which, in part, could have been explained by means of a real-time US business cycle indicator, such as the degree of capacity utilization in manufacturing. This result is robust to the specification of the estimating equation and to the considered business cycle indicator. An out-of-the-sample prediction exercise reveals that futures adjusted to take into account this time-varying component produce significantly better forecasts than those of unadjusted futures, of futures adjusted for the average forecast error and of the random walk, particularly at horizons of more than 6 months.
Keywords: E37; E44; G13; Q4; 330; forecasting; Futures; Oil; Ölpreis; Prognoseverfahren; Kapazitätsauslastung; Wirtschaftsindikator; USA